Improving High School Students’ Problem-Solving Skills in Ecosystem Learning through Problem-Based Learning Supported Instructional Videos - Putu Meta Oktaviani; Sindy Pratiwi; Miswandi Tendrita; Sutriani Kaliu; Ernawati Ernawati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Problem-Based Learning (PBL) has been shown to enhance higher-order thinking skills; however, its implementation still predominantly relies on worksheets, printed modules, or static media, which have not comprehensively facilitated all stages of the PBL process. Preliminary observations at senior high school (SMA Negeri 1 Toari and SMA Negeri 1 Latambaga) revealed that more than 60% of students experienced difficulties in identifying problems, and only about 35% were able to systematically formulate problem-solving strategies. Methodology: A Research and Development (R&D) approach based on the ADDIE framework was adopted in this study, encompassing the stages of analysis, design, development, implementation, and evaluation. Information was obtained through classroom observations, semi-structured interviews, expert validation procedures, as well as questionnaires administered to teachers and students to capture their responses. Findings: The results demonstrated that the instructional media developed in this study attained a validity index of 87.5%, which was classified as highly valid, while its practicality reached 90%, placing it within the highly practical category. Furthermore, the effectiveness analysis conducted using the Wilcoxon Signed-Rank Test produced a significance value of 0.000 (< 0.05), thereby confirming the effectiveness of the media in enhancing students’ problem-solving abilities. Contribution: The findings indicate that the PBL-based instructional video developed in this research was both feasible and effective in improving students’ understanding of problem-solving skills. The innovative contribution of this study is reflected in the instructional design of the video, in which learners are systematically directed through each phase of the PBL framework to facilitate the development of problem-solving abilities within biology learning